The Use of Nata de Coco Membrane as Biosensor Material - Tri Mulyono; Asnawati Asnawati; Indra Noviandri; Buchari Buchari (Jurnal ILMU DASAR, 2007)
Nata de coco has been characterized as filter toward glucose solutions. Standard nata de coco membrane can not be used as membrane because of variations of thickness. It has unequal weight if it was made thinner. Based on its character, nata de coco had been made in various incubation times. Three days incubation time membrane have passed up 76.84 % glucose, 61.15  Lm -2hr -1 flux/permeability. In Low concentration, it’s produced permeate 87% and decrease in increasing concentration. Structures of membrane morphology showed that existence of bovine serum albumin (BSA) in glucose solution possibility didn't influence determination of glucose in blood.